Embedded systems codesign under artificial intelligence perspective: a review. (21st October 2019) - Boutekkouk, Fateh
Intelligent embedded systems (IES) and their distributed versions, represent a novel and promising generation of embedded systems. IES have the capacity of reasoning about their external environments and adapt their behaviour accordingly. Such systems are situated in the intersection of two different branches, which are the embedded computing and the intelligent computing. On the other hand, intelligent embedded software (IESo) is becoming a large part of the engineering cost of intelligent embedded systems. IESo can include some artificial intelligence-based systems such as expert systems, neural networks and other sophisticated artificial intelligence (AI) models to guarantee some important characteristics such as self-learning, self-optimising and self-adaptation. Despite, the wide spread of such systems, some design challenging issues are arising. Designing a resource constrained software and at the same time intelligent is not a trivial task especially in a real-time context. To deal with this dilemma, embedded systems researchers have profited from the progress in semiconductor technology to develop specific hardware to support well AI models and render the integration of AI with the embedded world a reality.